Constraining Autonomy: How Bureaucratic Dysfunctions Impede Regional Financial Independence in a Decentralized Indonesia - Kamal, Kasmad; Darmadi, Dandi; Idrus, Iqbal Aidar (Universitas Teuku Umar, 2025)
This research aims to analyze how bureaucratic pathology serves as a fundamental impediment to the realization of regional financial independence in Indonesia. Employing a qualitative approach with a comparative case study method across six regions, enriched by international comparative analysis, this study identifies the institutional factors that systematically influence regional fiscal performance. The findings reveal five critical dimensions of dominant bureaucratic pathologies: excessive centralized control, slow budget planning processes, corruption and abuse of power, bureaucratic incompetence, and resistance to innovation. The study found that the manifestation of these pathologies varies among regions, contingent upon their level of development and governance capacity, thereby indicating the need for differentiated, rather than uniform, policy responses. International experiences from Brazil to Germany demonstrate the universality of these challenges. It is concluded that achieving genuine financial independence requires more than the mere transfer of formal authority; it necessitates the construction of a robust institutional foundation. The study recommends implementing support systems tailored to regional capacities, enhancing trans parency, promoting bureaucratic professionalism, and establishing citizen engagement mechanisms to build effective and accountable subnational governance, drawing lessons from successful reforms in countries such as Estonia and Rwanda.